Examination of Leader-Member Exchange and Employee Performance of Nurses - Özlem Özer (Association of Nurse Managers, 2019)
INTRODUCTION: The aim of this study is to examine the perception of nurses regarding leader-member exchange and employee performance and to investigate the impact of the level of leader-member exchange on employee performance. METHODS: The universe of the research is composed of nurses working in a public hospital in the province of Antalya. The sample was not selected in the study, tried to reach the whole universe and a total of 203 nurses were obtained. In the study, 'Leader-Member Exchange Scale' was used to measure leader-member exchange perceptions of the nurses and 'Employee Performance Scale' was used to measure their performance perceptions. In the analysis of the data, descriptive statistics, reliability analysis, correlation analysis, regression analysis, t test in two independent groups and one way analysis of variance (Anova) were used. The data were analyzed by SPSS program. RESULTS: According to the results of the research, it has been determined that the highest average among sub-dimensions of the level of leader-member exchange is the sub-dimension of professional respect, and that the average of employee performance is the highest. In the study, statistically significant differences have been established in the sub-dimensions of loyalty and contribution and the employee performance in line with the status variable in hospital (p<0.05). And it was determined that the scores of the manager nurses were higher. In compliance with the data obtained from the regresssion analyses, it has been determined that the whole sub-dimensions of the level of leader-member exchange explain %40.6 of the total variance which is on the employee performance. DISCUSSION AND CONCLUSION: The results show that leadership-member exchange sub-dimensions are important in improving the performance of nurses.